Prolonged Sinus Pause with Sleep Apnea Syndrome: A Case Report (Bangladesh Heart Journal, 2016)
Cardiac rhythm during sleep is influenced by the autonomic nervous system and various pathological states. Most arrhythmias that occur during sleep are detected incidentally on Holter monitoring, and are in fact benign. However, sometimes they may be an important clue to an underlying disorder requiring further investigation and treatment. Efforts should be given to recognize factors predisposing to sleeprelated arrhythmias; successful management of an underlying disorder can prevent and treat potentially dangerous cardiac rhythms. Here we describe a case of obstructive sleep apnea syndrome presenting with prolonged pause on Holter monitoring, which was corrected by continuous positive airway pressure (CPAP) therapy.Bangladesh Heart Journal 2015; 30(2) : 96-99